Concept of JFM Functioning and its Evaluation - Paulraj, S. (Indian Forester, 2012)
Although the JFM concept is becoming popular more and more all over India, there is no well defined methodology to evaluate the functioning of JFM. As a result, it is not possible to evaluate JFM functioning and to find out the level of success of the JFM. Therefore, an attempt has been made to bring out a concept paper on JFM that enables evaluation of JFM in a systematic manner. The concept and functioning of Joint Forest Management are discussed with reference to three systems operating in JFM - the Forest supporting system, Life supporting system and JFM supporting system. The inter-relationships among these three systems and the methodology of evaluating each system are discussed. The use of the methodology in evaluating the JFM functioning at local level and state level are also given. This paper will pave way for improving the evaluation method of JFM by making use of the concepts explained here.